Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2012)
An efficient high yielding improved method for the enantio- and diastereoselective cyclopropanation of chiral epoxides using triethylphosphonoacetate and base (Wadsworth-Emmons cyclopropanation) is reported. The utility of this protocol is illustrated by concise and practical synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II, a cyclopropane containing natural products.

Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II (vol 10, pg 6987, 2012) - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2020)